LED control of gene expression in a nanobiosystem composed of metallic nanoparticles and a genetically modified E. coli strain - Aratboni, Hossein Alishah; Rafiei, Nahid; Khorashad, Larousse Khosravi; Lerma Escalera, Albert Isaac; Balderas Cisneros, Francisco de Jesús; Liu, Zhaowei; Alemzadeh, Abbas; Shaji, Sadasivan; Morones Ramírez, José Rubén (BioMed Central Ltd., 2021)
Abstract Background Within the last decade, genetic engineering and synthetic biology have revolutionized society´s ability to mass-produce complex biological products within genetically-modified microorganisms containing elegantly designed genetic circuitry. However, many challenges still exist in developing bioproduction processes involving genetically modified microorganisms with complex or multiple gene circuits. These challenges include the development of external gene expression regulation methods with the following characteristics: spatial–temporal control and scalability, while inducing minimal permanent or irreversible system-wide conditions. Different stimuli have been used to control gene expression and mitigate these challenges, and they can be characterized by the effect they produce in the culture media conditions. Invasive stimuli that cause permanent, irreversible changes (pH and chemical inducers), non-invasive stimuli that cause partially reversible changes (temperature), and non-invasive stimuli that cause reversible changes in the media conditions (ultrasound, magnetic fields, and light). Methods Opto-control of gene expression is a non-invasive external trigger that complies with most of the desired characteristics of an external control system. However, the disadvantage relies on the design of the biological photoreceptors and the necessity to design them to respond to a different wavelength for every bioprocess needed to be controlled or regulated in the microorganism. Therefore, this work proposes using biocompatible metallic nanoparticles as external controllers of gene expression, based on their ability to convert light into heat and the capacity of nanotechnology to easily design a wide array of nanostructures capable of absorbing light at different wavelengths and inducing plasmonic photothermal heating. Results Here, we designed a nanobiosystem that can be opto-thermally triggered using LED light. The nanobiosystem is composed of biocompatible gold nanoparticles and a genetically modified E. coli with a plasmid that allows mCherry fluorescent protein production at 37 °C in response to an RNA thermometer. Conclusions The LED-triggered photothermal protein production system here designed offers a new, cheaper, scalable switchable method, non-destructive for living organisms, and contribute toward the evolution of bioprocess production systems.